2000
DOI: 10.1259/bjr.73.867.10817044
|View full text |Cite
|
Sign up to set email alerts
|

Radiation doses received in the UK Breast Screening Programme in 1997 and 1998.

Abstract: The mean glandular doses (MGDs) to samples of women attending for mammographic screening are measured routinely at screening centres in the UK Breast Screening Programme (NHSBSP). This paper reviews the data collected during screening in the NHSBSP in 1997 and 1998 for 23,752 films, using 171 X-ray sets, for 8745 women. Average MGD was 2.03 mGy per oblique film and 1.65 mGy per craniocaudal film, similar to the MGDs found previously in the NHSBSP for the years 1994 and 1995. MGD was found to increase with comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 6 publications
3
27
0
2
Order By: Relevance
“…Similar results are obtained by other authors [4,21]. For that reason median ± quartile were calculated as more appropriate descriptors.…”
Section: Patient Measurementssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results are obtained by other authors [4,21]. For that reason median ± quartile were calculated as more appropriate descriptors.…”
Section: Patient Measurementssupporting
confidence: 86%
“…Smans et al [18] and Young et al [21] reported even higher differences between the MGD from patient and phantom measurements. The former author found phantom doses lower than patient doses and the latter author found higher phantom doses exceeding by about 50% the patient doses.…”
Section: Phantom Measurementsmentioning
confidence: 92%
“…Furthermore, if screening with DBT results in a reduction in recall rate, as has been represent clinically encountered conditions, nor of a reasonable material to mimic its attenuation properties. Furthermore, although reports have included partial data on compressed thicknesses for the same breast in the craniocaudal and MLO views (28,29), a comprehensive study on this relationship still needs to be performed. Finally, it should be noted that MGD does not communicate the large variation in local dose deposition, which, as shown by Sechopoulos et al (14), can vary from 15%-400% of the MGD.…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned studies did not use conversion factors according to Dance (which are used in this study), but in Austra, Korea and Malaysia one used conversion factors according to Wu (Wu et al, 1991), in Sweden according to Rosenstein and in Iran according to Sobol (Sobol & Wu, 1997). Values of MGD dose for a complete mammographic examination in Bosnia and Herzegovina are 5,0 % higher in regard to results obtained from 300 patients in Malaysia (Jamal et al, 2003) and 7,8 % higher in regard to the most complete study (Young & Burch, 2000) conducted in the Great Britain which included 8745 patients. More than 70 % of all of mammographic diagnostic examinations was done with doses less than 3,2 mGy.…”
Section: Patient's Dosesmentioning
confidence: 97%
“…It is extremely important to examine a relation between projections (craniocaudal and mediolateral projection) during a mammographic diagnostic, compressed breast thickness and mean glandular dose received by a patient during one exposition and during the complete examination for two different age groups (Wall & Roberts, 1992;Gentry & De Werd, 1996;Heggie, 1996;Klein et al, 1997;Young, 2000;Young & Burch, 2000;Oh et al, 2003;Jamal et al, 2003;Sookpeng & Ketted, 2006;Bouzarjomehri et al, 2006;Tsapaki et al, 2008;Ciraj-Bijelac et al, 2010;Kunosic et al, 2010). Patients are divided into a group of younger patients (40 -49) and a group of older patients (50 -64), according to the European Protocol for Dosimetry in Mammography (Perry, et al, 2006).…”
Section: Patient's Doses For Two Different Age Groupsmentioning
confidence: 99%